IMPACT OF OTHER MEDICAL CONDITIONS ON PAIN AND FUNCTIONALITY FOLLOWING TOTAL HIP ARTHROPLASTY: A PROSPECTIVE COHORT STUDY. - Prabhat, Vinay; Guria, Abhishek; Topno, Rohit; Kundu, Sabyasachi (Student’s Journal of Health Research Africa, 2024)
Background Total hip arthroplasty is the procedure carried out for patients suffering from arthritis. Arthritis is a painful bone inflammation that severely affects the functional ability of the hip bone. Total hip arthroplasty helps in reduction of the painful inflammation and it also helps in restoring the functional ability of the hip bone Method This was a prospective study including individuals who underwent total hip arthroplasty at Rajendra Institute of Medical Sciences, Ranchi. The 30 patients participating in the study underwent the total hip arthroplasty. Patients were asked to follow up after 3 months, 6 months, 12 months, and 24 months of the surgery. Preoperatively, after the surgery and during the follow-up the hip bone was assessed using WOMAC score survey form 36. Results Comorbidities increased with age, affecting postoperative outcomes. Higher CCI values led to poorer functional improvements and more complications, sometimes necessitating conservative measures. Older patients and those with higher CCIs had higher complication rates and readmissions. CCI rose with age, from 0.29 for patients <40 to 5.42 for those >70. Significant improvements in WOMAC and SF-36 scores were seen at the third-month follow-up, but higher CCI patients declined after six months. Patients with CCI >3 had three surgical complications, while CCI 2 patients had two complications related to infection. No complications occurred in patients with CCI 0 and 1, but one patient with a higher CCI died. Conclusion From this study, it was found that the occurrence of comorbidity after the THA significantly decreased patient satisfaction. Also, the higher preoperative CCI resulted in the occurrence of comorbidity, delayed improvement, decreased recovery, increased rate of readmission, and decreased satisfaction of the patient. Recommendation This association can guide clinicians in taking appropriate steps to intervene in the occurrence of comorbidities and treatment of the comorbidities to improve patient satisfaction.